Integrating green manure and fertilizer reduction strategies to enhance soil carbon sequestration and crop yield: evidence from a two-season pot experiment - Zhang, Jun; He, Wei; Wei, Zheng; Chen, Yifei; Gao, Weichun (Frontiers in Sustainable Food Systems, 2025)
The excessive use of chemical fertilizers in agricultural production has led to diminishing returns, necessitating alternative methods to enhance soil fertility and reduce fertilizer dependency. One promising approach is the integration of leguminous green manure, which improves soil structure, enhances nutrient cycling, and supports sustainable farming practices. However, the application of green manure in systems with continuous fertilizer reduction remains underexplored. This study addresses this gap by investigating the effects of reducing nitrogen and phosphorus fertilizers (N-P) by up to 24% in conjunction with multiple cropping of soybean green manure on soil fertility, organic carbon fractions, and wheat yield. The research employed a pot experiment conducted over two wheat-growing seasons (March 2021 to July 2022) at an experimental station in Baoji, China. Treatments included CK (control, no fertilizer), CF (conventional fertilizer), and reduced N-P fertilizer applications by 6% (RF6), 12% (RF12), 18% (RF18), and 24% (RF24). Key findings revealed that RF12 had no significant impact on wheat grain yield compared to CF. The incorporation of soybean green manure significantly improved soil alkaline nitrogen by 22.3% and available phosphorus by 30.7%, while high-labile organic carbon (H-LOC) and microbial biomass carbon (MBC) increased by 34.5 and 29.6%, respectively. Additionally, a notable increase of 12.4% in soil organic carbon content was observed, suggesting enhanced carbon sequestration potential. This study provides valuable insights into sustainable agricultural practices by demonstrating that incorporating leguminous green manure alongside moderate fertilizer reduction can maintain crop yield, improve soil nutrient availability, and increase organic carbon content, thus supporting reduced reliance on chemical fertilizers and promoting long-term soil fertility and carbon sequestration.